2013
DOI: 10.1097/phh.0b013e318269e41c
|View full text |Cite
|
Sign up to set email alerts
|

Revenue Sources for Essential Services in Florida

Abstract: Revenue for ES is decreasing and is heavily reliant on noncategorical (discretionary) revenue. This study has important implications for continued reliance on ES as an organizing construct for public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…For this procedure, we sought to retain the model explaining the largest variance and in which the computed C(p) value is equal or close to the total number of predictor variables based on Mallows's C(p) criterion. 48,49 We confirmed the model selection results by checking our models against the Akaike information criterion and Bayesian information criterion. Results from Mallows's C(p) indicated that 16 control variables, along with the independent variable (rate of physical activity), should be retained because the selected model presented the best congruency between the total number of included predictors and the computed C(p) value.…”
Section: Selection Of Control Variablessupporting
confidence: 60%
“…For this procedure, we sought to retain the model explaining the largest variance and in which the computed C(p) value is equal or close to the total number of predictor variables based on Mallows's C(p) criterion. 48,49 We confirmed the model selection results by checking our models against the Akaike information criterion and Bayesian information criterion. Results from Mallows's C(p) indicated that 16 control variables, along with the independent variable (rate of physical activity), should be retained because the selected model presented the best congruency between the total number of included predictors and the computed C(p) value.…”
Section: Selection Of Control Variablessupporting
confidence: 60%
“…Although the authors did not identify any literature describing significant changes to federal funding opportunities or Congressional legislative changes leading toward greater state and local flexibility in funding use (R02), discourse was identified. A trend of decreasing federal and state funding prevailed during the 2012-2019 study period, leading to increased local “fiscal allocation” for public health as well as policy maker responses of spending down reserves, cutting spending, and raising taxes 14,23,35–40. The authors did, however, identify much discourse in literature that promoted local flexibility in expenditures, in contrast to the current state of primarily siloed and “categorical” funding, which restricts spending to predesignated functions and services 20,22,25,41–43.…”
Section: Resultsmentioning
confidence: 92%
“…A trend of decreasing federal and state funding prevailed during the 2012-2019 study period, leading to increased local "fiscal allocation" for public health as well as policy maker responses of spending down reserves, cutting spending, and raising taxes. 14,23,[35][36][37][38][39][40] The authors did, however, identify much discourse in literature that promoted local flexibility in expenditures, in contrast to the current state of primarily siloed and "categorical" funding, which restricts spending to predesignated functions and services. 20,22,25,[41][42][43] This discourse was determined to meet the authors' criteria of sustained influence to the practice community, even in lieu of official policy actions to improve flexibility.…”
Section: Substantial Documentation-r02 R03 and R07mentioning
confidence: 99%